2022
DOI: 10.13057/biodiv/d230336
|View full text |Cite
|
Sign up to set email alerts
|

Foliar stomata characteristics of tree species in a university green open space

Abstract: Abstract. Susilowati A, Novriyanti E, Rachmat HH, Rangkuti AB, Harahap MM, Ginting IM, Kaban NS, Iswanto AH. 2022. Foliar stomata characteristics of tree species in a university green open space. Biodiversitas 23: 1482-1489. Stomata, a gas regulatory system of leaves, provide a great chance to investigate the interaction between plants and their environment. Stomata consist of surrounded by two guard cells. Stomata are found in all parts of the plant that are exposed to the air, especially the leaves. In ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
(28 reference statements)
1
3
0
Order By: Relevance
“…The stomatal density of V. limbata in all treatments is considered low. This is in line with the report of Susilowati et al (2022) that stomata are categorized into 3 based on their density, which are low density (< 300 mm -2 ), medium density (300 to 500 mm -2 ) and high density (> 500 mm -2 ). Low stomatal density Figure 3.…”
Section: Stomatal Densitysupporting
confidence: 91%
“…The stomatal density of V. limbata in all treatments is considered low. This is in line with the report of Susilowati et al (2022) that stomata are categorized into 3 based on their density, which are low density (< 300 mm -2 ), medium density (300 to 500 mm -2 ) and high density (> 500 mm -2 ). Low stomatal density Figure 3.…”
Section: Stomatal Densitysupporting
confidence: 91%
“…mangostana complements the finding from the previous research done by Priya and Hari (2019). Hypostomatous and paracytic stomata were also reported on Garcinia brasilliensis (Cardoso et al, 2013), Garcinia cambogia (Sreelakshmi et al, 2014), Garcinia zhangpuensis (Wang et al, 2018), Garcinia dulcis (Begum, 2020), and Garcinia atroviridis (Susilowati et al, 2022). These findings supported the evidence that these two features of stomata are common in the Garcinia genus (Pathirana & Herat, 2004) and the Clusiaceae family (Metcalfe & Chalk, 1950).…”
Section: Resultssupporting
confidence: 57%
“…The widest stomata (37.62 µm) of G. mangostana var. mangostana was also reported in the previous study [16]. An important character such as stomata is purposely identified to define and classify species within the Garcinia taxa.…”
Section: Methodsmentioning
confidence: 54%
“…Paracytic stomata are common in Garcinia genus [15] and Clusiaceae family [1]. A previous study found the highest occurrence of paracytic stomata (91.46%) was observed in plant species, particularly Garcinia atroviridis followed by anomocytic (6.02%), anisocytic (1.20%), and diacytic (1.20%) in 83 trees species studied in green open space located in Universitas Sumatera Utara (USU) campus [16]. Other Garcinia species, Garcinia pedunculata, Garcinia lanceifolia, Garcinia morella and Garcinia xanthochymus exhibited a similar paracytic stomatal type [17].…”
Section: Methodsmentioning
confidence: 99%